Study of energy inflow - outflow pattern in paddy cultivation with specific reference to tillage treatments - JAYACHANDRAN S; Jayasree G. S; Sobhalatha P. K; Sureshkumar P. R; Er. Sathyajith Mathew (Guide) (Tavanur 1992 Department of Farm Power Machinery and Energy)
Study of energy inflow - outflow pattern in paddy cultivation with specific reference to tillage treatments
Study of energy inflow - outflow pattern in paddy cultivation with specific reference to tillage treatments